PENGGUNAAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING DAN PROJECT BASED LEARNING SEBAGAI UPAYA MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS (HOTS) PADA MATA PELAJARAN PRAKARYA DAN KEWIRAUSAHAAN KELAS XII IPS SMA NEGERI 1 MOTOLING - Sumangkut, Youla I. A.; Wuisang, Jerry; Kandori, Iwan (Jurusan Pendidikan Ekonomi Fakultas Ekonomi dan Bisnis UNIMA, 2024)
ABSTRACK Before the action was implemented, the average score for Class XII students' Creative Products and Entrepreneurship lessons was 66.67. After taking action in cycle I, the average student critical thinking ability score was 72.89. Furthermore, in cycle II the average critical thinking ability of students increased, namely 89.48. Before the action was carried out, the average critical thinking ability of students was in the low category with a completion level of 44% out of 27 students. In cycle I, after taking action, students' critical thinking skills were still in the low category with a completion level of 56% out of 27 students. In cycle II, after carrying out further action as a result of reflection in cycle I, students' critical thinking abilities were in the medium category with a completion level of 93%, with a total of 25 students passing out of a total of 27 students. Keywords Keywords: Problem Based Learning Model, Project Based Learning, Critical Thinking Ability